LANGUAGE STYLE ANALYSIS IN THE LYRICS OF THE SONG CAK CULAY NABUY-NABUY BY MUHAMMAD YUSUF (STILISTIC STUDY) - Habibansyah, Afeby Ade (Transpublika Publisher, 2024)
This study aims to identify, analyze and reveal the meaning of language style in the lyrics of the song